Brief Report: A Regulatory Variant in CCR6 Is Associated With Susceptibility to Antitopoisomerase‐Positive Systemic Sclerosis. Issue 12 (December 2013) - Koumakis, Eugénie; Bouaziz, Matthieu; Dieudé, Philippe; Ruiz, Barbara; Riemekasten, Gabriella; Airo, Paolo; Müller‐Nurasyid, Martina; Cusi, Daniele; Matucci‐Cerinic, Marco; Melchers, Inga; Salvi, Erika; Strauch, Konstantin; et al.
<x xml:space="preserve">Abstract</x> Objective Recognition of the well‐known pleiotropism of autoimmune genes supports the concept of a shared pathogenesis across autoimmune diseases such as rheumatoid arthritis (RA) and systemic sclerosis (SSc). Studies have reproducibly demonstrated an association between susceptibility to RA and polymorphisms of the CCR6 gene, a surface marker for Th17 cells, and the causal variant was recently identified. The present study was thus undertaken to investigate whether CCR6 polymorphisms could also be associated with susceptibility to SSc. Methods Twelve tag single‐nucleotide polymorphisms (SNPs) of CCR6, including the known RA‐associated SNP rs3093023, were genotyped in a total of 2, 411 SSc patients and 7, 084 healthy individuals from 3 European populations (France, Italy, and Germany). Meta‐analyses of the data were performed to assess whether an association exists between CCR6 polymorphisms and susceptibility to SSc or its main subtypes. Direct sequencing of DNA was performed to ascertain whether the functional dinucleotide polymorphism of CCR6 previously identified in RA (CCR6DNP) was also present in SSc. Results Combined analyses revealed an association between the rs10946216 SNP and SSc susceptibility (odds ratio [OR] 1.13, 95% confidence interval [95% CI] 1.05–1.21, adjusted P [Padj] = 0.026). The rs3093023 A allele and rs10946216 T allele were in high linkage disequilibrium, and both were found to confer disease susceptibility in the antitopoisomerase‐positive subset of SSc patients (OR 1.27, 95% CI 1.13–1.42, Padj = 1.5 × 10−3 and OR 1.32, 95% CI 1.17–1.48, Padj = 9.0 × 10−5, respectively, relative to healthy controls). Direct sequencing of the DNA of 78 individuals supported the hypothesis that the regulatory dinucleotide CCR6DNP could be the causal variant in SSc. Conclusion The results of this study establish CCR6 as a new susceptibility factor for antitopoisomerase‐positive SSc, as demonstrated in 3 European Caucasian populations, confirming the notion that SSc and RA could conceivably share autoimmune risk alleles. The results also suggest a potential role of the interleukin‐17 pathway in SSc.